2009
DOI: 10.1094/cchem-86-2-0204
|View full text |Cite
|
Sign up to set email alerts
|

Wet‐Milling Characteristics of 10 Lines from Germplasm Enhancement of Maize Project Compared with Five Corn Belt Lines

Abstract: The use of corn (Zea mays L.) hybrids with high grain yield and starch extractability has steadily increased in the processing industry. In light of widespread corn seed industry participation in the Germplasm Enhancement of Maize Project (GEM), which seeks to enhance exotic germplasm, future hybrids may contain more exotic sources in genetic backgrounds. It is necessary to establish and monitor physical, compositional, and milling characteristics of the new exotic breeding materials to determine the processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 11 publications
6
14
6
Order By: Relevance
“…However, industrial yields for steepwater solids (5%–10%) can be higher because industrial steep times can be considerably longer (30–48 hr) with more solids leached (Taboada‐Gaytan et al, ). The germ yields ranged from 3.08% to 10.05% (db) and were within the published range for other maize samples (Dowd, ; Fox et al, ; Milašinović et al, ; Mussolini et al, ; Singh et al, ; Taboada‐Gaytan et al, , ). Germ yields connote the ease of the separation of the germ at an industrial level, but do not necessarily represent the amount of this component in the maize kernel (Singh & Eckhoff, ).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…However, industrial yields for steepwater solids (5%–10%) can be higher because industrial steep times can be considerably longer (30–48 hr) with more solids leached (Taboada‐Gaytan et al, ). The germ yields ranged from 3.08% to 10.05% (db) and were within the published range for other maize samples (Dowd, ; Fox et al, ; Milašinović et al, ; Mussolini et al, ; Singh et al, ; Taboada‐Gaytan et al, , ). Germ yields connote the ease of the separation of the germ at an industrial level, but do not necessarily represent the amount of this component in the maize kernel (Singh & Eckhoff, ).…”
Section: Resultssupporting
confidence: 84%
“…Starch yields of wet‐milling of white and yellow (more) maize have been reported by various authors. Fox et al () reported a range of 50.9%–60.0% (db) for yellow maize hybrids, Taboada‐Gaytan et al () published a range of 55.1%–63.9% (db) for the Corn Belt lines, and Singh et al () measured a range of 47.8%–61.9% (db) for their samples. The Brazilian maize samples (Mussolini et al, ) ranged from 61.15% to 62.79% (db), the ZP hybrids (Milašinović, Radosavljević, Dokić, & Jakovljević, ) yielded a range of 58.8%–69.0% (db), and a range of 62.60%–70.17% (db) was obtained (Singh et al, ; Vignaux, Fox, & Johnson, ) for five Pioneer yellow maize hybrids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As described in our previous studies (Taboada-Gaytan et al 2009, 2010, 10 GEM lines of five germplasm sources, each source represented by a relatively high and low starch yield line from a wetmilling screening done by the private GEM cooperator Cerestar (Hammond, IN; now acquired by Cargill, Minneapolis, MN) were selected. The lines had 50% or 25% exotic genetic background from Argentina, Chile, Cuba, Florida, and Uruguay and were grouped according to starch yield from wet milling as high-starch exotic lines (HSEL): AR16035:S19-285-1-B (AR285), CH05015: N15-182-1-B (CH182), CUBA117:S1520-562-1-B (CU562), FS8B(T): N1802-35-1-B (FS35), and UR13085:N0215-11-1-B (UR11); and low-starch exotic lines (LSEL):AR16035:S19-227-1-B (AR227), CH05015:N15 -143-1-B (CH143), CUBA117: S1520-153-1-B (CU153), FS8B(T):N1802-32-1-B (FS32), and UR13085:N0215-14-1-B (UR14).…”
Section: Genetic Materialsmentioning
confidence: 99%